The moderating effect of alexithymia on the relationship between stress and cyberchondria - Zhou, Yi; Dai, Lisha; Deng, Yunlong; Zeng, Hongling; Yang, Lifeng (Frontiers in Psychiatry, 2022)
Objectives The pandemic has increased the level of perceived stress and provided a fertile soil for Cyberchondria. This study aims to investigate the relationship between stress, cyberchondria, and alexithymia. Methods This cross-sectional study used convenience sampling to carried out on a total 1,117 college students (female/male:536/581; mean age: 19.95 ± 1.32). Cyberchondria Severity Scale (CSS), Toronto Alexithymia Scale (TAS) and Short Depression Anxiety Stress Scales (DASS-21) were used to assessed the present study variables. Results Significant differences emerged for CSS scores by gender (t = 3.74, p < 0.01) and had any comorbid disease (t = 2.47, p < 0.05), The Pearson correlation showed Cyberchondria has a significant positive correlation with stress and alexithymia (r = 0.50, p < 0.01, r = 0.36, p < 0.01). Furthermore, the regression analysis described that stress (β = 0.50, p < 0.01) and alexithymia (β = 0.36, p < 0.01) were the significant positive predictors of cyberchondria. Moreover, moderation analysis showed that alexithymia significantly strengthened the association between stress and cyberchondria (F = 107.20, p < 0.01). Conclusion The study will help medical practitioners to understand how stress and alexithymia can cause an increase in cyberchondria. This will help them to elaborate operational indications for prevention and psychological support.